Skyrmion phase and competing magnetic orders on a breathing kagomé lattice - Max Hirschberger (Nature Portfolio, 2019)
Understanding and controlling the skyrmion lattice (SkL) phase facilitates its versatile applications. Here the direct observation of a SkL phase with large topological Hall effect in centrosymmetric Gd3Ru4Al12 is reported, which is stabilized by thermal fluctuations and magnetic field without Dzyaloshinskii-Moriya interactions.